SWIMBLADDER ON FISH TARGET STRENGTH - Sunardi Sunardi; Anton Yudhana; Jafri Din; Raja Bidin Raja Hassan (Universitas Ahmad Dahlan, 2008)
This paper discusses of Target Strength (TS) for the Selar boops (Oxeye scad) and Megalaspis cordyla (Torpedo scad), the most commercially fish in Malaysia. TS can be determined from in situ measurements and calculation using acoustic fish model. TS value, depth, and position (x-y-z) of fish targeted can be viewed from echogram using FQ-80 Analyzer by in situ measurement. X-ray imaged can be deployed to develop the acoustic fish model. The percentage of length and upper surface area for swimbladder to body fish of Selar boops more than Megalaspis cordyla can be measured after X-ray process. The percentage of width and volume of swimbladders to its each body are no significantly difference for both fish. These data of swimbladder physic are supports the result from in situ measurement which TS of Megalaspis cordyla have more than Selar boops.